“las ilustraciones literarias en el desarrollo cognitivo de los niños y niñas de 2do de educación básica paralelo “c”, de la unidad educativa Carlos Cisneros parroquia veloz, cantón Riobamba, provincia de Chimborazo año lectivo 2016-2017.” - Carrasco Vergara, Ana Fabiola (2017)
The investigation topic refers to the literary illustrations which are constituted by chapters. In the chapter I the problem of investigation is formulated departing from the general target to go on to the specific targets and to reach a fundamental intention of the investigation. In the chapter II the theoretical frame develops announcing the precedents and theories of several authors on the literary illustrations and the cognitive development to optimize the knowledge in the reading. In the chapter III there is evident the methodological frame in which it is verified and decides that a design of qualitative investigation has been used; with a type of documentary and not experimental bibliographical inquiry, as well as of the level of exploratory and descriptive investigation, the opinion poll was realized by a population of 36 children and 4 teachers of the Educational Unit Carlos Cisneros; for this work there was designed a card of observation and a questionnaire that were applied. In the chapter IV the skill was applied to the children and girls of the second year of basic education, understanding that this methodology helps to the cognitive progress to improve its workmanship. The obtained information was tabulated and was charted, obtaining excellent information about the use of the illustrations and its contribution in the cognitive development. Chapter V specifies the conclusions and recommendations coming to a result once finished the investigation that the secondhand literary illustrations of a correct way and suitable potency the cognitive development of the children and one raises recommendations that they help in the solution of the raised disadvantage.